THIRD INTERNATIONAL FORUM OF CARDIOLOGISTS AND INTERNAL MEDICINE SPECIALISTS MARCH 18–20TH 2014, MOSCOW (Кардиоваскулярная терапия и профилактика)
Third International Forum of Cardiologists and Internal Medicine Specialists March 18–20th 2014, Moscow.